Pengaruh Pelayanan Karyawan PT Putera Bangun Melalui Whatsapp Terhadap Konsumen Perumahan Taman Sukamulya Indah Cikarang - Ehsan dinata; Viona Naomi Istiqomah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of digital communication technology has significantly transformed the way companies interact with their customers, especially through platforms like WhatsApp as a service medium. PT Putera Bangun, a property developer, utilizes WhatsApp to communicate effectively with residents of Taman Sukamulya Indah Housing in Cikarang. This study aims to analyze the impact of employee service quality delivered via WhatsApp on resident satisfaction. The theoretical framework of this study is grounded in Interpersonal Communication Theory (Littlejohn & Foss, 2008), Media Richness Theory (Daft & Lengel, 1986), Servqual Theory (Parasuraman, Zeithaml, & Berry, 1988), Organizational Communication Theory (Robbins, 2005), and Customer Satisfaction Theory (Oliver, 1980). A descriptive quantitative approach was employed using a survey method. The population consisted of residents of Taman Sukamulya Indah who use PT Putera Bangun’s WhatsApp services, with a purposive sample of 64 respondents. The research instrument was a closed-ended questionnaire using a 5-point Likert scale measuring four dimensions of service quality: responsiveness, reliability, empathy, and assurance. Data were collected through both online and face-to-face questionnaires and analyzed using descriptive statistics and simple regression. The findings reveal that most respondents rated PT Putera Bangun’s WhatsApp services as fairly good across all service dimensions. However, the majority of responses fell into the “fairly agree” category, indicating room for improvement—particularly in response speed, consistency of information, and the overall positive impression of the services. These results affirm the relevance of interpersonal communication and media richness theories in digital service contexts and demonstrate how improving service quality can significantly enhance customer satisfaction and loyalty..